Dramatists and Poets as Agents of Yoruba Culture: A Study of Hubert Ogunde’s and Femi Abodunrin’s Works - Akinola, Ogungbemi Christopher (Imbizo, 2021)
In many ways, people reveal their language, culture, identity, traditions and beliefs through the contents and themes of their performance arts, in addition to other identity moulding and retaining paraphernalia. However, for failing to fit into the mould of the West, the culture and traditions of peoples of African descent have been erroneously misunderstood and, in some cases, even scorned. Beyond the aesthetics and the utilisation of Africa’s oral traditions in passing down African histories and ways of life to current and future generations, the Yoruba artist’s utilisation of performative art forms such as drama and poetry to first, reassure the Yoruba themselves and then, educate the world about Africa’s cultures has become necessary. This article is an exploration of the narratives and nuances in the works of Hubert Ogunde and Femi Abodunrin as tools in the propagation of a Yoruba cultural outlook. It further takes a closer look into how the works of these writers could influence new narratives about Yoruba creativity as cultural agency from Africa’s own perspective. The study reveals the relevance of the artistic, performative and literary works of Ogunde and Abodunrin as agencies of propagation of Yoruba culture in the twenty-first century.